From Platform Specification to Product Simulation: A Novel Application of SysML v2 in Product Line Engineering - Wagner, Heinrich; Arestova, Anna; Portenlänger, Lukas; German, Reinhard; Zuccaro, Claudio (2024 IEEE International Conference on Recent Advances in Systems Science and Engineering (RASSE), 2024)
Product Line Engineering (PLE) methodologies have already established their significance within the domain of Model-Based Systems Engineering (MBSE) and are gradually being adopted in the industry. While Systems Modeling Language (SysML) models are already pivotal as the Single Source of Truth in product development, the use of PLE methodologies has been limited, particularly in terms of simulation and validation. Our approach extends the application of PLE from the specification of complex product platforms to the simulation of individual products, ensuring a consistent view of variability across different development phases and artifacts. This is facilitated by the adoption of SysML version 2 (v2), the SysML v2 API, and a newly developed model transformation for the OMNeT++ simulation environment. The proposed methodology is validated through a feasibility study focused on a railway in-vehicle network system. The integration of SysML v2 with OMNeT++ creates a seamless workflow that supports the entire product development lifecycle, enhancing modeling capabilities and providing detailed insights into product performance and behavior. This approach not only manages the complexity of modern engineering systems but also ensures that aspects of product variability are consistently addressed. The study demonstrates the practical applicability and benefits of this approach, leading to more efficient, accurate, and high-quality product developmen